Adad-nirari III and Semiramis: The Stelae of Saba’a and Rimah - Page, Stephanie
the stele of Adad-nirari III and Nergal-ereš (cf. 30:290) and its implications for a possible co-regency of Adad-nirari III with Sammu-ramat.